2021
DOI: 10.1002/emp2.12429
|View full text |Cite
|
Sign up to set email alerts
|

Assessing COVID‐19 pneumonia—Clinical extension and risk with point‐of‐care ultrasound: A multicenter, prospective, observational study

Abstract: contributed equally to this study.Registration: This study is registered with trialregister.nl, Trial NL8497.Funding and support: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.Background: Assessing the extent of lung involvement is important for the triage and care of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…They concluded that the extend of pulmonary involvement detected by lung ultrasound were associated with poor outcome, admission duration, and disease severity. 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the extend of pulmonary involvement detected by lung ultrasound were associated with poor outcome, admission duration, and disease severity. 37 …”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 , 34 , 35 Although existing data suggest the extent of pulmonary findings in POCUS correlate with disease severity, there are few studies formally assessing the predictive capabilities of POCUS in COVID‐19. 36 , 37 …”
Section: Introductionmentioning
confidence: 99%
“…Typical LUS ndings have a good correlation with COVID-19 PCR positivity. This has been well studied and published previously 29 , 30 , 31 , 32 , 33 , 34 . Preserved A-lines in all 6 zones made the diagnosis of COVID-19 related respiratory failure extremely unlikely 35 .…”
Section: Discussionmentioning
confidence: 77%
“…A 10–5 MHz linear transducer or 5–3 MHz curvilinear transducer with lung examination setting was used. The lung ultrasound protocol consisted of a structured assessment of 6 zones of each hemithorax [ 34 ]. The recently modified criteria from Mathis et al were used to diagnose PE in COVID-19 patients [ 14 , 18 ].…”
Section: Methodsmentioning
confidence: 99%